P.042 A novel SOD1 mutation associated with rapidly evolving lower motor neuron syndrome and MR ventral nerve root enhancement. (June 2022) - Perera, T; Bencsik, C; Pfeffer, G; Mobach, T
Abstract : Background: Mutations in the Cu/Zn superoxide dismutase 1 (SOD 1) gene are estimated to cause 20% of familial ALS and 1-2% of sporadic cases. Accurate gene variant classification of novel mutations in amyotrophic lateral sclerosis (ALS) has deepened our understanding of clinical phenotypes, provided pathologic insights, and is crucial to incorporating emerging therapies. Methods: We describe a case of a 75-year-old female who presented with a rapidly progressive lower motor neuron syndrome leading to flaccid quadriparesis and complete loss of independence over a five month period. Results: Genetic testing demonstrated a heterozygous variant of uncertain significance in the SOD1 gene with a g > c point mutation at position 382 that has been described in one other patient in available literature. MR of the lumbar spine demonstrated abnormal smooth nerve root enhancement. Conclusions: This novel mutation in the SOD1 gene may be associated with a rapidly progressive phenotype of sporadic ALS. Ventral nerve root enhancement should not exclude a diagnosis of ALS especially in the absence of nodularity or nerve enlargement.